ANALYSIS OF HIGHER ORDER THINKING SKILLS (HOTS) IN MATHEMATICAL PROBLEM SOLVING BASED ON REVISED BLOOMS’ TAXONOMY VIEWED FROM GENDER EQUALITY - Ernawati Ernawati; Baharullah Baharullah (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
This study aims to determine the description of the results of the analysis of higher order thinking skills in mathematics problem solving based on revised Bloom's taxonomy viewed from gender equality. The subject of the research is two students of SMPN 1 Takalar selected using a purposive sampling technique. The type of research used is descriptive research with a qualitative approach. The description was obtained by analyzing the tests of higher order thinking skills in mathematical problem solving. In this study, instruments in the form of questions test higher order thinking skills based on revised Bloom's taxonomy and the interview guideline. Data collection techniques in the form of test, interview, observation, and documentation. The data analysis technique was data reduction, data presentation, and conclusion drawing/verification. The results of the research show that subjects can use their skills even though still not achieved optimally. Both subjects use almost all aspects of thinking skills based on the revised Bloom's taxonomy, either directly or to bridge the subject in constructing the higher order thinking skills. It shows the difference in students' higher order thinking skills from each category, namely the male and female categories.